Cyclic iRGD peptide as a dual-functional on–off gatekeeper of mesoporous nanocontainers for targeting NRP-1 and selective drug release triggered by conformational conversion. (21st December 2018) - Lee, Jeonghun; Oh, Eun-Taex; Lee, Jinyoung; Kang, Taehyeong; Kim, Ha Gyeong; Kang, Hansol; Park, Heon Joo; Kim, Chulhee
Abstract : A cyclic iRGD peptide as a dual-functional on–off gatekeeper on the surface of MSNs is prepared for specific NRP-1 targeting and selective drug release by conformational conversion. Abstract : Adopting conformational conversion of a peptide as a trigger to control on–off gatekeeping on the surface of mesoporous silica nanoparticles has several advantages. Here, we designed a dual-functional cyclic peptide with an iRGD sequence as a stimulus-responsive on–off gatekeeper on the surface of mesoporous silica nanocontainers. The cyclic peptide gatekeeper with an intramolecular disulfide bond between the two cysteine units at both terminals of the peptide sequence exhibited selective drug release triggered by stimulus-induced conformational conversion. Furthermore, the iRGD sequence of the cyclic peptide gatekeeper enhanced the intracellular uptake and therapeutic efficacy of the nanoparticles by specifically binding with NRP-1 receptor on the surface of target cancer cells.